1998
DOI: 10.1192/pb.22.5.309
|View full text |Cite
|
Sign up to set email alerts
|

Access to health records: psychiatric patients and patients with diabetes compared

Abstract: Thisstudy was undertaken to assess whether psychiatric patients respond more adversely to reading their own records than non-psychiatric patients. Seventy-three psychiatric out-patients and 84 out-patients with diabetes were posted their main clinical summary with a questionnaire about it. For seven of the eight questions, more than 70% of both patient groups gave favourable ratings. However, the psychiatric patients gave significantly less favourable responses than the patients with diabetes on five of the ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The only result that approached statistical significance indicated that record-informing may have a favorable effect on perceptions of therapist attentiveness. This trend is generally consistent with previous findings that clients respond favorably to being able to access their records (Jha et al, 1998;Laugharne & Stafford, 1996;Roth et al, 1980). This study failed to replicate previous research studies that found that note-taking during sessions has detrimental effects on perceptions of therapists (Hickling et al, 1984;Miller, 1992).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The only result that approached statistical significance indicated that record-informing may have a favorable effect on perceptions of therapist attentiveness. This trend is generally consistent with previous findings that clients respond favorably to being able to access their records (Jha et al, 1998;Laugharne & Stafford, 1996;Roth et al, 1980). This study failed to replicate previous research studies that found that note-taking during sessions has detrimental effects on perceptions of therapists (Hickling et al, 1984;Miller, 1992).…”
Section: Discussionsupporting
confidence: 91%
“…Despite the lack of research to date that has directly examined the effect of informing clients of their right to access their records on perceptions of a therapist, multiple studies have found that clients respond positively to reviewing their records with their psychologist (Jha, Bernadt, Brown, Sawicka, & Stein, 1998; Laugharne & Stafford, 1996; Roth, Wolford, & Meisel, 1980). Client access to their records has been shown to give clients greater understanding and autonomy (Laugharne & Stafford, 1996).…”
mentioning
confidence: 99%
“…They were requested to return the completed questionnaire in a self-addressed and stamped envelope. The questionnaire was adapted from an earlier study (Jha et al, 1998). It comprised 10 questions about the written summary related to the diagnosis in the letter, reaction to the diagnosis, accuracy of the content of the letter, omissions of important points, upset caused by reading the letter, wrong emphasis, understanding, helpful information, outlook and assistance received (Appendix).…”
Section: Questionnairementioning
confidence: 99%
“…Some early research on this topic suggested both apprehensiveness among health personnel and surprise over reported benefits (Atkinson & Clay, 1993;Kosky & Burns, 1995;Roth et al, 1980). In a comparison between diabetes patients and psychiatric patients, Jha, Bernadt, Brown, Sawicka, and Stein (1998) found that even though patients in the diabetes group benefitted more from reading parts of the medical record than did those in the psychiatric group, both nevertheless experienced advantages from reading it. Fisher, Bhavnani, and Winfield (2009) gave access to their medical files to 43 patients in primary care, including 10 mental health patients, and observed that because they came to consultations more prepared, their freedom to consult their medical records had improved the quality of their care.…”
Section: Psychiatric Resistance To Transparencymentioning
confidence: 99%